Pre Treatment Air Gambut Dengan Tanah Lempung Lahan Gambut Dan Aplikasi Membran Ultrafiltrasi Sistem Aliran Cross Flow Untuk Menyisihkan Zat Organik Dan Kekeruhan - Marzona Erlita Sari; Syarfi Daud; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Usage of peatland clays as liquid coagulant in pre treatment process still have a problem, so needed a process using ultrafiltration membranes. The purpose of this study was to determine the removal efficiency of organics matter and turbidity in pre treatment process using liquid coagulant of peatland clays with variation coagulant doses and learn the flux and rejection of organics matter and turbidity in peat water in processing using cross flow system ultrafiltration membrane without and with pre treatment. This research was conducted by varying the dose of liquid coagulant by 40 ml, 50 ml and 60 ml to 1000 ml of peat water and variations ultrafiltration membrane operating pressure of 0.5 bar, 1 bar and 1.5 bar. The result showed the best coagulant dosage is 40 ml, the highest flux obtained at processing using ultrafiltration membranes with a pre treatment at a pressure of 1.5 bar and highest rejection of organic matter and turbidity obtained on processing using ultrafiltration membranes with a pre treatment at a pressure of 0.5 bar respectively amounted to 96.34% and 100%.Key words: organic matter, peatland clays, peat water, turbidity, ultrafiltration membrane.